Different activities of the adenovirus types 5 and 12 E1A regions in transformation with the EJ Ha-ras oncogene. - Jochemsen, A G (1986)
We have compared the capacities of the E1A regions of nononcogenic adenovirus type 5 (Ad5) and highly oncogenic Ad12 to cooperate with the EJ bladder carcinoma Ha-ras-1 oncogene in the transformation of primary baby rat kidney cells. Both E1A regions, when cotransfected with the Ha-ras oncogene, transformed the primary cells with a low frequency. Ad5 E1A plus Ha-ras-transformed cells differed in phenotype from cells transformed by Ad12 E1A plus Ha-ras. The cells expressing Ad5 E1A appeared highly transformed and practically failed to adhere to plastic. This phenotype may be due to the virtually complete absence of fibronectin gene expression in these cells. In contrast, the cells expressing Ad12 E1A were flatter and adhered to plastic, whereas fibronectin gene expression was reduced but not absent. The oncogenic potential of the two types of E1A plus ras-transformed cells was tested by their injection into both athymic nude mice and weanling syngeneic rats. The Ad5 E1A plus ras-transformed cells were found to be highly oncogenic in both animal species, whereas the Ad12 E1A plus ras-transformed cells were only weakly oncogenic in both syngeneic rats and nude mice. The difference in oncogenic potential of the Ad5 E1A plus ras- and the Ad12 E1A plus ras-transformed cells is discussed in terms of the different capacities of the Ad5 and Ad12 E1A-encoded proteins to modulate cellular gene expression.